2014
DOI: 10.1556/crc.42.2014.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Root trait characteristics and genotypic response in wheat under different water regimes

Abstract: Under limiting water resources, root system response of genotypes to soil-water conditions with enhanced shoot biomass holds the key for development of improved genotypes. Based on the hypothesis of root biomass contribution to higher yields under limiting conditions which might be attributed to the root system plasticity of genotypes, a set of thirty-four genotypes were evaluated under three moisture regimes in a pot experiment for root system traits. Total root dry matter had a positive association with tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Polle et al [31] reported that drought-tolerant wheat genotypes condition themselves after imposed drought stress. Several researchers also documented that plant growth parameters such as shoot and root length and their biomasses were significantly affected by drought stress created by PEG osmoticum (plural: osmotica) and their significance for drought stress screening in wheat [24,49,61,63,[81][82][83][84][85] and barley [57] have been extensively studied. In the present study, the effect of genotypes (G), treatment (Trt), and their interaction (Trt × G) was highly significant (p < 0.001) for the studied growth attribute traits except for SDW (Table 1) which is also in agreement with previous reports in wheat [31,43,81,86] and rice [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polle et al [31] reported that drought-tolerant wheat genotypes condition themselves after imposed drought stress. Several researchers also documented that plant growth parameters such as shoot and root length and their biomasses were significantly affected by drought stress created by PEG osmoticum (plural: osmotica) and their significance for drought stress screening in wheat [24,49,61,63,[81][82][83][84][85] and barley [57] have been extensively studied. In the present study, the effect of genotypes (G), treatment (Trt), and their interaction (Trt × G) was highly significant (p < 0.001) for the studied growth attribute traits except for SDW (Table 1) which is also in agreement with previous reports in wheat [31,43,81,86] and rice [87].…”
Section: Discussionmentioning
confidence: 99%
“…The root is the main organ of the plant for water and mineral acquisition from the soil. Deprivation of water in the soil causes a root system plasticity [84] which further reduces root proliferation and ultimately inhibits the upstream water and mineral transportation and largely reduces grain yield [56]. More recently, Ahmed et al [58] reported that wheat plants with a deeper root growth and suppressed shoot system are an indicator of drought tolerance, as they have increased root to shoot ratios.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Red Fife, which exhibited the lowest belowground C allocation had several adverse and opposing responses to compost relative to genotypes with higher R:S ratios. The multiple interactions between genotype and soil treatments for various plant growth parameters suggest that under low fertility conditions genotypic root plasticity will be an important factor affecting agroecosystem performance following the adoption of new management regimes, such as the use of organic inputs [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, genotypes with overall higher R:S ratio and root length also had the greatest response in their R:S ratio and length under compost additions ( Table 1 , Fig 1 ). Thus, there may be sufficient inherited genotypic variation that can be used to select for phenotypic traits that will be responsive to soil health improvements [ 63 ]. Plant functional traits are often used to predict how a plant will perform under a changing environment [ 82 , 83 ] and it may be that traits such as R:S could be used to better predict genotype responses to changes in soil management [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological traits for water limited environments include those improving canopy temperature, photosynthetic capacity, stay-green, stomatal conductance water uptake (Reynolds et al 2012) while traits for improving heat tolerance are light intercepting traits, photo-protection systems, radiation use efficiency and, partitioning of total assimilates to yield (Cossani and Reynolds 2012). Physiological traits integrate many responses such as source-sink balance, vascular movement of water, root biomass (Jain et al 2014) and has been useful for phenotypic selection as secondary traits (Lopes and Reynolds 2010).…”
Section: Introductionmentioning
confidence: 99%